The nutrient value of banana peel fermented by tape yeast as poultry feedstuff - Koni, Theresia Nur Indah; Foenay, Tri Anggarini Yuniwaty; Asrul, Asrul (Faculty of Animal Science, Universitas Brawijaya, 2019)
This study aims to evaluate the effect of different tape yeast levels as inoculum in the banana peels fermentation process to the nutritional content. This study used an experimental method with a Completely Randomized Design (CRD) in one way ANOVA with 4 treatments and 4 replications. Treatments based on differences in the addition of tape yeast, all treatments were incubated for 6 days. The four treatments are (P0) Banana peel without the addition of yeast tape; (P1) Banana peel with the addition of yeast tape 1.5%; (P2) Banana peel with the addition of 3.0% yeast tape; (P3) Banana peel with the addition of 4.5% yeast tape. The measured variables were dry matter, crude protein, crude fat, crude fiber, calcium, and phosphorus content. Data were analyzed by analysis of variance and followed by Duncan's multiple range test to measure any significances. The results showed that the level of yeast tape significantly increased crude protein, crude fat, calcium and phosphorus (P<0.05), and significantly reduced crude fiber of banana peel (P<0.05. However the level of yeast tape has no significant effect on the dry matter content of banana peels. Conclusion tape yeast level of 4.5% can increase levels of crude protein, crude fat, calcium and banana skin phosphorus. The highest reduction in crude fiber in the use of yeast tape 3%